11. Motivation and Creativity in Working with Pop/Rock/Jazz Bands of Secondary and High School Level - Cojocaru-Spînu Ramona Mariana (Sciendo, 2022)
The national offer of extra-curricular activities started including in the past few years the pop/rock/jazz bands as part of non-formal education, either in institutions like Children's Palace or in private music schools, as a direct consequence of the manifested interest of the students in this direction. The teachers coordinating secondary and highschool level bands are challenged to find ways to keep the students engaged and motivated for longer periods of time. Student's motivation is related to their need of being listened to and to be consulted in regards of the decisions that concern the ensemble they belong to and to their image that this activity is a project-based one and requires time, and in this project they can contribute with abilities from other domains. This article suggests some of the key points that can help a band teacher to maintain a high level of motivation in students for a longer time.